Interpretation and Affect in Found Footage Remakes: Martin Arnold’s Pièce Touchée - Nace Zavrl (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2016)
The found footage remakes of experimental filmmaker Martin Arnold transform intimate domestic scenes from classical Hollywood into a series of neurotically repetitive back-andforward gyrations. Exploring hidden psychological and socio-political subtexts, Arnold’s pièce touchèe (1989) offers a subversion of cinematic representational codes, as well as a sensorily engrossing experience to the spectator. This paper focuses on the graphic, visceral, rhythmic, and musical qualities of pièce touchée, examining the film’s moments of direct kinetic delight and disarming hilarity. Further, the paper interrogates the bodily experience of pièce touchée through an examination of additive rhythm, audio-visual looping, and flickering repetition. Arnold’s basic remaking techniques (editing, mirroring, and repetition) work to create an engagingly complex sampling piece, where the spectator’s interpretative and critical activities are based on a pre-narrative, pre-language, audio-visual intensity, and an affective fascination with the reappropriated source material.